Infrastructure, clinical leadership, and organizational culture enhancing KRIS implementation readiness in hospitals - Siti Zuhroh; Ellya Niken Prastiwi; Intan Silviana Mustikawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The implementation of the Standard Inpatient Class (KRIS) policy presents challenges for hospitals in ensuring equitable service delivery. Organizational readiness depends not only on adequate physical infrastructure but also on an adaptive organizational culture and strong clinical leadership to guide change. As a referral hospital, RS BM must ensure alignment across organizational components to meet KRIS standards sustainably. This study analyzes the influence of infrastructure quality and clinical leadership on organizational readiness for KRIS implementation, with organizational culture as an intervening variable. A quantitative cross-sectional design was used, involving 136 healthcare and medical personnel working in the inpatient units of RS Bhakti Mulia. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) to examine relationships among variables. Infrastructure quality and organizational culture significantly and positively affect organizational readiness. Clinical leadership, while not directly influencing readiness, has a significant positive effect on organizational culture. KRIS readiness at RS BM is shaped by infrastructure quality, clinical leadership, and organizational culture, with culture acting as the main mediator. The hospital shows strong readiness but still faces gaps in progress monitoring, inpatient room layout and privacy, leadership direction, and team participation. Strengthening monitoring mechanisms, improving room design according to KRIS standards, enhancing clinical leadership capacity, and fostering a collaborative organizational culture are essential to support comprehensive and sustainable KRIS implementation